Seminested PCR for detection and identification of Candida species directly from blood culture bottles - (:unkn) unknown (EDIZIONI INT SRL, 2010)
We investigated the performance of a seminested PCR (snPCR) assay carried out directly from overnight incubated blood culture bottles of 50 newborn intensive care unit (NICU) patients with suspected candidemia and compared these, for sensitivity, specificity and reliability with results from blood cultures. All positive blood cultures (n=17) yielded positive results for snPCR, which detected the same Candida species, as did the yeast isolates of which 13 were C. parapsilosis and 4 were C. albicans. With both assays showing 32 negative samples and one sample positive with snPCR but negative with blood culture, sensitivity and specificity of snPCR were 100% and 97%, respectively. The patient with contradictory results exhibited a positive blood culture one week later yielding the same species as identified by snPCR. These are the first data demonstrating that snPCR from overnight blood culture bottles can be a potential tool for rapid detection and identification of Candida species, allowing follow-up of the gold standard blood culturing, as well.
Keywords: Blood culture; Candidemia; Diagnosis; Seminested PCR (snPCR); REAL-TIME PCR; ANTIFUNGAL SUSCEPTIBILITY; RAPID IDENTIFICATION; SURVEILLANCE PROGRAM; STREAM INFECTIONS; ASSAY; GENE; DNA; ORTHOPSILOSIS; AMPLIFICATION